Features of professional career motivation of the applicants enrolled in undergraduate pedagogical programs - Faina M. Kremen; Sergei A. Kremen (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The preparation of pedagogical staff who meet the demands of a dynamically developing world is a strategic task that determines the well-being of the society and the state. One of the effective ways to address this task may be to attract motivated applicants to university programs in pedagogical education who are aware of the significance and multi-faceted nature of the teacher’s work, are oriented towards the personal development of students, and are ready to embrace modern technologies and approaches. In this regard, the research focused on identifying the motivations for choosing a pedagogical profession, including career orientations, is especially relevant. The aim of this research is to identify the features of motivation for a professional career among applicants admitted to pedagogical programs and to determine the relationship between their career orientations and socio-demographic and motivational-professional characteristics. The empirical methods of the study included E. Schein’s «Career Anchors» methodology and questionnaire surveys. The study involved 107 applicants and 107 second-year students at Smolensk State University. The results obtained indicate stable trends in the motivation for choosing a pedagogical profession, expressed in the career orientations of «service» and «job stability», which are predominant among the subjects of both studied groups. In addition, applicants who consciously chose a pedagogical profession demonstrate readiness for professional development and overcome difficulties. The indicators of applicants who have experience in pedagogical activities and plans for work in the field, as measured by the scales of «professional competence» and «challenge», are statistically higher than those of individuals with predominantly external motivation for enrollment. These research findings confirm the feasibility of pre-professional training for future teachers.